A human acellular dermal matrix coated with zinc oxide nanoparticles accelerates tendon repair in patients with hand flexor tendon injuries in zone 5 of the hand - Seyedeh-Sara Hashemi; Mohsen Pirmoradi; Alireza Rafati; Mehdi Kian; Ali Akbar Mohammadi; Mohamad Ali Hoghoughi (BioImpacts)
Introduction: Flexor tendon injuries are common and require surgery. Acellular dermal matrix (ADM) is a natural graft used to repair tissues, though infections represent the primary cause of its therapeutic failure. In this study, zinc oxide nanoparticles (ZnO-NPs) were coated on the ADM in order to add antibacterial potential as well as enhance healing properties. Also, the produced ADM/ZnO-NPs graft was applied to accelerate fifth zone flexor tendon repair following the reconstructive surgery. Methods: Morphological, mechanical, cell viability, and antibacterial tests were performed to evaluate the physical and biological properties of the fabricated ADM/ZnO-NPs graft. For clinical evaluations, 20 patients with a flexor tendon injury in zone 5 were randomly divided into control and treatment with ADM/ZnO-NPs groups (n=10 each). The control group had routine reconstructive surgery, while the other group received the ADM/ZnO- NPs graft during their surgery. Postoperative functional outcomes were evaluated 4, 6, and 8 weeks following the tendon repair surgery according to the Buck-Gramcko II criteria. Results: The ADM/ZnO-NPs had natural derm specifications as well as dense and integrated morphology with intermediate antibacterial properties. According to the Buck- Gramcko II criteria, the postoperative functional outcome scores were significantly higher in the ADM/ZnO-NPs group in comparison with the control group at 4 (P<0.01), 6 (P<0.01), and 8 (P<0.001) weeks after the surgery. Conclusion: The present findings revealed that the ADM/ZnO-NPs graft can accelerate the healing of the damaged tendon without common post-operative functional complications and adhesions following the tendon repair surgery. However, more comprehensive clinical trials are still needed.